Filtered reality: exploring the motives and socio-demographic factors of smartphone beauty filter usage among university students in Ghana - Praise Woeyram Anani; Francis Dadzie Mintah; Awura Amma Adomaa Danso; Emmanuel Wiston Churcher (Cogent Arts & Humanities)
In the era of digital transformation and the widespread adoption of social media, the use of smartphone beauty filters has significantly altered how individuals present themselves online. This study investigates the use of these filters among university students in Ghana, aiming to understand the motivations behind their usage, their prevalence, and their impact on self-perception and identity. Utilizing a comprehensive survey method, the research reveals that a substantial number of students frequently use multiple beauty filters, driven by the desire to enhance their appearance and gain social approval. The findings highlight a notable gender disparity, with female students showing a higher propensity towards filter usage, reflecting societal beauty standards and pressures. Additionally, the study underscores the psychological implications of filter dependency, including decreased self-acceptance and altered self-perception. This research addresses a significant gap in the literature by focusing on the underexplored context of Ghanaian university students and their digital behaviors. The study emphasizes the need for educational institutions and policymakers to implement digital literacy programs and mental health interventions that address the responsible use of beauty filters, fostering a balanced approach to digital self-representation that safeguards the mental and emotional well-being of young individuals.